Plan de cierre del bloque 2 de la cantera cenaca perteneciente a la empresa holcim Ecuador S.A., ubicada en la parroquia Chongón, cantón Guayaquil, provincia del Guayas. - Enríquez Mora, Byron Gonzalo (2015)
Block 2 is located within the mining area Cenaca, it has an extension of 1.5 km, it is located in the immediate vicinity of the piedmont of the southern end - east of the mountain range Chongon, Cerro Blanco Sector. The area is bordered to the North with Cerro Blanco Protected Forest, to the east with Block 1, to the west with the block 3 and to the South with the premises of the Guayaquil plant. The Guayaquil Plant (formerly Cerro Blanco Plant) is located in the southern sector of Block 2, it is also property of Holcim Ecuador, is the installation of clinker and cement production. The area under study is located in the Ecuadorian coast and the mean temperatures are between 25 ° to 31 °, and there are two seasons: the rainy season between December through April and the dry season from May to November. The natural areas are covered by a more or less dense forest; its wildlife is composed of mammals, reptiles and amphibians there are also observed birds and invertebrates such as crustaceans, arachnids and insects. The Geology is formed by limestones of the San Eduardo formation, siltstones of the Formation “Las Mazas” and of the formation Ancon. The course of the sedimentary layers has East-West direction and the dips are to the south. There have been established the following angles: the overall angle 60 degrees and the angle of exploitation slopes 80 degrees, for the study area (Block 2). The productive processes for the exploration and exploitation of materials (limestone, clay and limonite), carried out in Block 2, are the following: • Exploration and surveys. • Exploitation site selection. • Site assessment and location determination of loads. • Drilling. • Explosives and blowing up charging. • Transport of fragmented material. • Primary shredding (Guayaquil Plant). The activities referred to in the closure plan are:  In the quarry: modeling of slopes, control of surface runoff, signaling installation, analysis of the best alternative for the closure of the quarry.  On the roads: arrangement of the access roads, signaling installation.  In residue management and others: debris removal and final disposition of the residues. The sequence of phases to be followed for the closure and abandonment plan will be the following:  Phase 1: Previous studies.  Phase 2: post-closure period. (This will include the monitoring PM10, PM2.5 and noise for at least 2 years.  Phase 3: Stage of abandonment. Considering the Block 2 as a micro-basin, which are: Tree planting and rehabilitation, within a total of 242 hectares. Banks exploitation as in the slopes between banks, using in this last case, when required, the methodology of the geo-cells. The total cost of the proposed restoration would be from USA $ 323.234.00 considering all the activities to be undertaken. Finally, conclusions and recommendations are made to the effect that the proposal of the restoration of the Block 2 is feasible.